2022
DOI: 10.1038/s41523-022-00480-4
|View full text |Cite
|
Sign up to set email alerts
|

Multianalyte liquid biopsy to aid the diagnostic workup of breast cancer

Abstract: Breast cancer (BC) affects 1 in every 8 women in the United States and is currently the most prevalent cancer worldwide. Precise staging at diagnosis and prognosis are essential components for the clinical management of BC patients. In this study, we set out to evaluate the feasibility of the high-definition single cell (HDSCA) liquid biopsy (LBx) platform to stratify late-stage BC, early-stage BC, and normal donors using peripheral blood samples. Utilizing 5 biomarkers, we identified rare circulating events w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Figure 1 shows a schematic of the overall data science pipeline. It is important to note that NDs often exhibit small numbers of rare cells across the range of channel types 18 , making a rigorous statistical treatment necessary to distinguish SCLC from ND.
Figure 1 HDSCA3.0 Workflow.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows a schematic of the overall data science pipeline. It is important to note that NDs often exhibit small numbers of rare cells across the range of channel types 18 , making a rigorous statistical treatment necessary to distinguish SCLC from ND.
Figure 1 HDSCA3.0 Workflow.
…”
Section: Resultsmentioning
confidence: 99%
“…After washing in TBS for 5 min, the cells were stained with 0.1 μg/mL DAPI (Life Technologies Corp, CA, USA) in TBS for 10 min, washed in TBS for 5 min, dipped in distilled water, mounted with a glycerol-based media, and coverslipped. Slides were then imaged as described below. …”
Section: Methodsmentioning
confidence: 99%
“…Among these, the third-generation high-definition single-cell assay (HDSCA3.0) workflow provides the ability to identify and characterize epithelial, mesenchymal, endothelial, and hematopoietic cells, as well as large EVs. A study demonstrated that, beyond CTCs, assessing a wider range of circulating events enhanced the ability to categorize normal donors, EBC, and MBC patients into distinct groups ( 133 ).…”
Section: Challenges Of a Multiparametric Approachmentioning
confidence: 99%